Análisis exergo-ambiental a los motores aéreos comerciales de tipo turbofan - Castro Hernández, Sergio (Universidad Autónoma Metropolitana, 2018)
In this work an exergo-environmental analysis of the turbofan engine GE 90-115B, based on the exergoeconomic and environmental analysis, where exergy and environmental sustainability assessment indicators are used to evaluate the performance of the aircraft engine to the conditions that are submitted during a flight. Since the aircraft engines are indispensable in the air sector, as well as in the economic development of the countries; for this reason the objective of this work is to develop an exergoenvironmental methodology to evaluate the performance of the GE 90-115B engine at different flight conditions, based on the irreversibilities, exergoeconomic costs and emissions generated. The study of the performance of the GE 90-115B turbofan engine in this work begins with the energy analysis at differents ambient flight conditions, compressor pressure ratios, turbine inlet temperatures and bypass ratios. To determine the loss of exergy in the system (irreversibility), an exergy analysis is carried out which helps to better predict the performance of the aircraft engine through the exergy efficiencies of the equipments that composes the turbofan. In addition to this, the use of exegetical sustainability indicators such as the potential for exergy improvement, the exergetic sustainability index, the environmental effects factor, among others, are useful to determine the sustainability of the turbofan engine, these in function on the exergy analysis. To perform a more complete analysis of aircraft engine performance, the exergoeconomic analysis is implemented, an important study due to the economic losses that are reflected by the generation of irreversibility of the system, as well as the cost of generating the thrust, which is the objective of the aircraft engine. For the development of the exergo-environmental study of the turbofan engine GE 90-115B, two flight, take-off and cruise conditions were taken; for take-off conditions, the engine operates at a Mach 0.2 flight at ambient conditions of pressure and temperature of 1.013 bar and 15 ° C, respectively, while on a cruising flight, the Mach is 0.85 and the environmental conditions of pressure and temperature are 0.29 bar and 218.8 K. As a result of the energy analysis for take-off conditions, the specific thrust and specific fuel consumption of the turbofan engine GE 90-115B are 228.44 Ns/kg and 0.44 kg/(Nh) respectively, also it was found that the decrease in ambient temperature, as well as the increase in the inlet temperature to the turbine generates an increase in the specific thrust of the aircraft engine. From the exergy analysis, it was found that combustion gases are the main generators of irreversibilities, which have a value of 342.82 kJ/kg. On the other hand, the equipment with the greatest generation of irreversibility of the turbofan engine GE 90-115B is the combustion chamber with a value of 285.32 kJ/kg. By means of the exergo-economic analysis, the costs of thrust, fuel and waste were obtained, which were 0.028 $/s, 0.042 $/s and 0.013 $/s, respectively; while the total global warming potential, obtained through environmental analysis is 0.098 kgCO2eq/(kNh) and in cruise condition it is 0.113 kgCO2eq/(kNh).; En este trabajo se realiza un análisis exergo-ambiental a la turbina de gas aérea de tipo turbofan GE 90-115B, basado en el análisis exergoeconómico y ambiental, donde se emplean indicadores de evaluación de sustentabilidad exergética y ambiental para evaluar el desempeño del motor aéreo a las condiciones que son sometidos a lo largo de un vuelo. Ya que las turbinas de gas aéreas son indispensables en el sector aéreo, así como en el desarrollo económico de los países; por este motivo el objetivo de este trabajo es desarrollar una metodología exergo-ambiental para evaluar el desempeño del motor de aviación GE 90115B a diferentes condiciones de vuelo, en función de las irreversibilidades, costos exergoeconómicos y emisiones generadas. El estudio del desempeño del turbofan GE 90-115B en este trabajo, inicia con el análisis energético a diferentes condiciones ambiente de vuelo, relación de presiones del compresor, temperatura de entrada a la turbina y relación de bypass. Para determinar la pérdida de exergía en el sistema (irreversibilidad), se realiza un análisis exergético al sistema, con este se predecir de mejor manera el desempeño del motor mediante las eficiencias exergéticas de los equipos que componente al turbofan. Aunado a esto, la utilización de indicadores de sustentabilidad exergética, tales como el potencial de mejoramiento exergético, el índice de sustentabilidad exergética, el factor de efectos ambientales, entre otros, son útiles para determinar la sustentabilidad del turbofan, estos se obtiene en función del análisis exergético. Para realizar un análisis más completo del desempeño del motor se implementa el análisis exergoeconómico, estudio importante debido a las pérdidas económicas que se reflejan mediante la generación de irreversibilidades del sistema, así como el costo de la generación del empuje, que es el objetivo del motor. Para el desarrollo del estudio exergo-ambiental del turbofan GE 90-115B se toman dos condiciones de vuelo, despegue y crucero; para las condiciones de despegue, el motor opera a un Mach de vuelo de 0.2 a condiciones ambientales de presión y temperatura de 1.013 bar y 15 °C, respectivamente; y para vuelo crucero, el Mach es de 0.85 y las condiciones ambientales de presión y temperatura son de 0.29 bar y 218.8 K. Como resultados del análisis energético para condiciones de despegue, el empuje específico y el consumo específico de combustible del turbofan GE 90-115B son de 228.44 Ns/kg y 0.44 kgcomb/(Nh) respectivamente; asimismo, se comprobó que la diminución de la temperatura ambiente, y el aumento en la temperatura de entrada a la turbina genera un incremento en el empuje específico del motor. Del análisis exergético, se encuentra que los gases de combustión generan 342.82 kJ/kg de irreversibilidades al enviarse al medio ambiente, la cámara de combustión genera 285.32 kJ/kg, y es el equipo del GE 90-115B que genera mayor irreversibilidades Mediante el análisis exergo-económico se obtuvieron los costos de la generación de empuje, combustible y residuo, los cuales fueron de 0.028 $/s, 0.042 $/s y 0.013 $/s, respectivamente; y el potencial de calentamiento global total, obtenido mediante el análisis ambiental, es de 0.098 kgCO2eq/(kNh) a condiciones de despegue y a vuelo crucero es de 0.113 kgCO2eq/(kNh).